2016
DOI: 10.1590/2177-6709.21.2.065-072.oar
|View full text |Cite
|
Sign up to set email alerts
|

The effect of canine disimpaction performed with temporary anchorage devices (TADs) before comprehensive orthodontic treatment to avoid root resorption of adjacent teeth

Abstract: Objective: The aim of this study was to evaluate the movement of impacted canines away from the roots of neighboring teeth before full-mouth bracket placement, performed by means of TADs to decrease undesired side effects on adjacent teeth. Methods: The study sample consisted of 34 palatally impacted canines, being 19 in the experimental group and 15 in the control group. In the experimental group, before placement of brackets, the impacted canine was erupted by means of miniscrews. In the control group, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 24 publications
(26 reference statements)
1
48
0
1
Order By: Relevance
“…In our case, prior use of high forces to retract the upper canines bilaterally on a 0.016 ″ NiTi wire resulted in such "roller coaster" effects. In the recent decade, many studies have shown a surge in the usage of TADs as direct anchorage for correction of transmigrated lower canines [11], upper [12], and molar uprighting [13] with the aid of sectional mechanics to nullify the unwanted side effects which accompany the use of archwire-guided mechanics or the usage of opposing dental components as anchorage.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, prior use of high forces to retract the upper canines bilaterally on a 0.016 ″ NiTi wire resulted in such "roller coaster" effects. In the recent decade, many studies have shown a surge in the usage of TADs as direct anchorage for correction of transmigrated lower canines [11], upper [12], and molar uprighting [13] with the aid of sectional mechanics to nullify the unwanted side effects which accompany the use of archwire-guided mechanics or the usage of opposing dental components as anchorage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a special traction method was necessary. The orthodontic treatment included three specific characteristics: the use of a heavy orthodontic reinforced anchorage (1.2″ stainless steel wire) [17], the use of continuous tensile forces produced by the NiTi closed coil springs, and the use of wire extensions (hooks) derived from the anchor unit that allowed control of the traction direction and prevented contact of the coil springs with the gingiva. The purpose of this treatment protocol was to avoid any undesirable effect on the maxillary incisors.…”
Section: Discussionmentioning
confidence: 99%
“…Root resorption of the maxillary incisors has been evaluated mainly on radiographs and using scoring systems. Length, area, and volume assessments have been reported by only a few studies using CBCT [1719]. This method allows the determination of changes to the structures surrounding the impacted canine, including the resorption produced in the incisor root.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of the permanent canine in the arch, after the normal eruption timing, leads clinicians to suspect canine impaction and that has to be con rmed by a clinical evaluation of the patient and a radiographic assessment. The approaches to the management of impacted canines are many, but the preferred approach typically involves surgical exposure and guided orthodontic eruption [2].…”
Section: Introductionmentioning
confidence: 99%
“…Temporary Anchorage Devices (TADs), and cantilevers with a Ttitanium Molybdenum Alloy (TMA) sectional represent alternative methods for anchoring the system: a TAD is a mini screw temporarily xed to the bone for the purpose of enhancing orthodontic movement, either by supporting the reactive unit (indirect anchorage) or by obviating the need for it (direct anchorage), and is subsequently removed after use [2]. A number of clinical studies and reviews have investigated the stability of TADs for acting as stable anchor units [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%